2006
DOI: 10.1007/s00221-006-0782-2
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic arm cycling produces a non-specific signal that suppresses Soleus H-reflex amplitude in stationary legs

Abstract: Rhythmic arm cycling significantly suppresses Hoffmann (H-) reflex amplitude in Soleus muscles of stationary legs. The specific parameters of arm cycling contributing to this suppression, however, are unknown. Between the arms or legs, movement results in suppression of the H-reflex that is specifically related to the phase of movement and the locus of limb movement. We speculated that the effects of arm movement features on H-reflexes in the leg would be similar and hypothesized that the Soleus H-reflex suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 47 publications
6
39
0
Order By: Relevance
“…This finding confirmed previous findings that the soleus H-reflexes were not phase-dependently modulated during cyclic movement of the arm (Frigon et al 2004;Loadman and Zehr 2007). However, other previous studies indicate that interlimb neural communication is phase-dependently modulated during rhythmic movement.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding confirmed previous findings that the soleus H-reflexes were not phase-dependently modulated during cyclic movement of the arm (Frigon et al 2004;Loadman and Zehr 2007). However, other previous studies indicate that interlimb neural communication is phase-dependently modulated during rhythmic movement.…”
Section: Discussionsupporting
confidence: 92%
“…Oscillatory movement of the foot modulated H-reflex excitability in the forearm muscle (Baldissera et al 2002;Cerri et al 2003;Borroni et al 2004). The H-reflex in the soleus muscle, an ankle extensor, was depressed during rhythmic arm cycling (Frigon et al 2004;Loadman and Zehr 2007;Dragert and Zehr 2009;Hundza and Zehr 2009) and during rhythmic arm swing (Hiraoka 2001;Hiraoka and Iwata 2006).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Understanding the status of the nervous system function after stroke is crucial in advancing effective rehabilitative practice. We previously showed that rhythmic arm cycling can activate descending pathways to modulate lumbar spinal cord activity (Dragert and Zehr 2009;Frigon et al 2004;Hundza and Zehr 2009;Loadman and Zehr 2007;Zehr et al 2004b). Recently this observation was extended to stroke participants where a similar but reduced effect was observed even in those with spasticity (Barzi and Zehr 2008).…”
Section: Translational Implications For Rehabilitationmentioning
confidence: 87%
“…In addition, phase-dependent modulation found in muscles of all four limbs during rhythmic movement is suggestive of coupling between segmental spinal networks [12,13,14,15,16]. Regulation of rhythmic arm and leg movement is supported by somatosensory linkages in the form of interlimb reflexes [12,17,18] and neural coupling between lumbar and cervical spinal cord networks [10,19,20,21,22]. …”
Section: Introductionmentioning
confidence: 99%